Biased Atmospheric, Sub-Atmospheric, and Low-Pressure Air Plasmas for Material Surface Improvements - Ueda, Mario; Kostov, Konstantin Georgiev [UNESP]; Oliveira, Rogerio de Moraes; Savonov, Graziela da Silva; Mello, Carina Barros; Fernandes, Bruno Bacci (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This paper deals with some important aspects of recent research related to atmospheric, sub-atmospheric (SA), and low-pressure plasmas. It calls attention to the definition of the pressure ranges in which they are divided to avoid misconceptions in the literature. Pulsed bias applied to elements inside the plasma can lead to important effects such as ion implantation, nitriding, sputtering, heating, and diffusion, which can result in some of the effective applications in surface engineering such as plasma immersion ion implantation (PI3), plasma nitriding, magnetron sputtering, and so on. Electric fields are essential for the production of different types of plasma, either ac, dc, or pulsed ones, as seen in RF, self-sustained, glow, and high-voltage glow discharges, for example. The interrelation between the bias pulse, mean-free path, and Paschen law is examined, seeking for further improvement of processing of the material surface being used in many modern technologies. Results on PI3 in the low and near SA pressures, as well as their applications in metals, are also discussed.
Keywords: Aerospace industry; corrosion; friction; plasmas